A Correction of the Genealogy of the Mamikonyans Princely Family - Vardanyan, Argishti (History and Culture, 2021)
Being one of the largest ministerial houses of early medieval Armenia, Mamikonyan`s dynasty attracted the attention of historians. However, there is a lot of reliable information in the sources. The 10th century historian Mesrop VayotsDzoreci mentions without any basis that Vartan, Vasak and Vahan Mamikonyans were the sons of Artavazd. And due to this circumstance, the further researchers considered them the sons of Artavazd. However, a detailed examination of the sources shows that Artavazd and Vasak Mamikonyans belonged to a family, not a father and a son. When Artavazd was proclaimed commander as a child in 338 , Vasak and  his brothers were in adulthood and Vasak was already nanny of Prince Arshak  then. And Artavazd, as a son of commander Vache Mamikonyan and a  representative of the senior branch, received the command and   the Mamikonyans dynasty from Khosrov Kotak , by which the king maintained the order of seniority.
Keywords: Mamikonyans; Artavazd; Vasak; Vache; Khosrov Kotak; Pavstos Buzand; Arshak II; historians; Catholicos